PENGARUH KARAKTERISTIK TERHADAP KINERJA PERAWAT PELAKSANA DI RUANG PERAWATAN INTENSIF RUMAH SAKIT KELAS A DAN B DI INDONESIA - Widaningsih, Widaningsih (Indonesian Journal of Nursing Health Science, 2016)
Abstract Nursing care development as integral of healthcare system made an improvement for nurseâs performance especially in intensive care unit. This research focused on nurseâs performance level based on their characteristics those are gender, age, length of work, training experiences, and educational background. Samples were nurses who work at class A and B hospital in Indonesia (722 respondents). This research utilized F-test and simple regression analysis. Findings revealed that characterictis influenced nurseâsperformance in intensive care unit (p-value= 0,045and determinant coefficient =1,8%). The implication of this research gave impact in hospital regulation towards nursesâ performace measurement in intensive care unit.Â Keywords: Nurseâs characteristics, performance, intensive care